Premalignant Lesions of the Oral Cavity: An Update - Aluckal, Eby; Li, Rachelle; Pei, Louise; Lee, Amy; Al-Shma, Sarah; Abraham, Abe (Journal of Orofacial Research, 2022)
Pre-malignant lesions or precancerous lesions are diseases that should be diagnosed at an early stage. Leukoplakia, erythroplakia, oral submucous fibrosis, and lichen planus are the most common premalignant lesions. These lesions should be diagnosed early to prevent the risk of malignant transformation if left untreated, in which treatment would be difficult. The most common etiology includes smoking, alcohol, and areca nut chewing. A wide variety of treatment modalities are available including topical and systemic corticosteroids, retinoids, and surgical intervention.